ABOUT DIFFUSIVE TRANSFER OF THERMAL ENERGY AND MASS OF COMPONENTS IN THERMODYNAMICS HEAT-RESISTANT SYSTEMS - Ivanov, Victor; Skachkov, Victor; Nesterenko, Tatiana; Kharchenko, Аlеksandr (Scientific Journal "Metallurgy", 2022)
Thermodynamics of irretrievable processes of transfer of energy and mass of matter is the special scientific direction, which examines equalition of the second principle of thermodynamics as starting mathematical model for balance of energy and mass of matter in the elementary volume of the thermodynamics system during it co-operating with an environment. In accordance with positions of thermodynamics of irretrievable processes motive forces of processes of transfer of warmth and mass of matter are by vectors and according to principle Curie their fully possible combination, id est force which predetermines stream of thermal energy can to entail a mass stream and back to front. The closed thermodynamics heat-resistant system which interchanges thermal energy and mass of components with an environment is examined. The noted process is limited by absence of convective constituent of process of transfer in the system. The volume of the system does not change during a diffusive transfer and by treason of en-thalpy in the system, as by the result of treason of thermal energy and concentration of mass, it is possible to neglect. The mathematical design of diffusive transfer of thermal energy and mass of components in the thermodynamics heatresistant system at pres-ence of and to absence of cross effects is executed.